Modulating hemoglobin allostery for treatment of sickle cell disease: current progress and intellectual property. (1st February 2022) - Pagare, Piyusha P.; Rastegar, Aref; Abdulmalik, Osheiza; Omar, Abdelsattar M.; Zhang, Yan; Fleischman, Andrew; Safo, Martin K.
ABSTRACT: Introduction: Sickle cell disease (SCD) is a debilitating inherited disorder that affects millions worldwide. Four novel SCD therapeutics have been approved, including the hemoglobin (Hb) modulator Voxelotor. Areas Covered: This review provides an overview of discovery efforts toward modulating Hb allosteric behavior as a treatment for SCD, with a focus on aromatic aldehydes that increase Hb oxygen affinity to prevent the primary pathophysiology of hypoxia-induce erythrocyte sickling. Expert Opinion: The quest to develop small molecules, especially aromatic aldehydes, to modulate Hb allosteric properties for SCD began in the 1970s; however, early promise was dogged by concerns that stalled support for research efforts. Persistent efforts eventually culminated in the discovery of the anti-sickling agent 5-HMF in the 2000s, and reinvigorated interest that led to the discovery of vanillin analogs, including Voxelotor, the first FDA approved Hb modulator for the treatment of SCD. With burgeoning interest in the field of Hb modulation, there is a growing landscape of intellectual property, including drug candidates at various stages of preclinical and clinical investigations. Hb modulators could provide not only the best chance for a highly effective oral therapy for SCD, especially in the under-developed world, but also a way to treat a variety of other human conditions.